2020
DOI: 10.1097/md.0000000000021228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kinect exergames on balance training among community older adults

Abstract: Background: Recent years have witnessed wide applications of exergames to balance training among the older adults. However, research concerning balance training with the use of Kinect for Xbox has remained scarce. While previous studies have shown the positive effects of exergames on improving balance and preventing falling among the older adults, there has been a paucity of empirical evidence supporting the superiority of Kinect exercise to conventional exercise over balance training among the ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 59 publications
(55 reference statements)
4
59
0
1
Order By: Relevance
“…All the 20 studies were randomized control trials. Twelve studies used the two-arm design, including one intervention arm and one control arm [ 4 , 21 , 23 , 29 , 30 , 32 38 ]. Six studies used a three-arm design, of which four included two intervention arms and one control arm [ 22 , 28 , 39 , 40 ], and two included one intervention arm and two control arms [ 31 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the 20 studies were randomized control trials. Twelve studies used the two-arm design, including one intervention arm and one control arm [ 4 , 21 , 23 , 29 , 30 , 32 38 ]. Six studies used a three-arm design, of which four included two intervention arms and one control arm [ 22 , 28 , 39 , 40 ], and two included one intervention arm and two control arms [ 31 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The other six studies which assessed falls efficacy only had the assessments at baseline and immediately following the intervention [ 4 , 21 , 32 , 37 , 41 , 42 ]. Two studies had the immediately post-intervention assessment and one additional follow-up assessment (i.e., 1-year follow-up and 4-week follow-up, respectively) to measure the balance control [ 33 , 39 ], and the other 16 studies only implemented an immediately post-intervention assessment [ 4 , 21 23 , 28 32 , 35 , 36 , 38 , 40 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Park et al [ 37 ] indicated that simulated exercises by smart Xbox Kinect could improve the TUG test among people with hemiplegia. Yang et al [ 45 ] also stated that VR exercises had impacts similar to those of real exercises, and might enhance balance. They concluded that virtual exercises could be a suitable substitute for real training.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Microsoft Kinect motion sensor is an accurate input device; thus, it allows precise tracking and real-time feedback of user performance [46]. The Microsoft Kinect sensor is proposed to be a feasible and effective tool for training concurrent physical and cognitive components in older adults, with the aim of reducing the intrinsic causes (ie, physical and cognitive) of falls [47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%